Testament of Sindh - "Korejo, M. S." (Karachi, 2002)
Among the problems facing Sindh today, ethnic militarism, sectarian extremism, and political terrorism have acquired menacing proportions. The book is an attempt to seriously and frankly analyse the current problems of Sindh.
Keywords: Conflict